Analysis of Financial Structure on Profitability and Non-Financial Performance in Industrial Companies - Supardi Supardi; Sriyono Sriyono; Sigit Hermawan (Jurnal Manajemen Indonesia, 2023)
Non-financial performance can be used to determine the success of the company and show the growth of a company. This study aims to examine and analyze the effect of Financial Structure (Working Capital, Asset Structure, and Operating Leverage) on Profitability and Non-Financial Performance in Industrial Companies. The sampling method used is the census method, which is a comprehensive sampling of 15 companies with a 3-year research period from 2019 to 2021. Method A the analysis is with method Partificial Least Square (PLS) using the Smart program PLS 2.0. The results of the analysis show that working capital and asset structure have an effect on profitability. Working capital, asset structure and operating leverage have no effect on non-financial performance. Profitability has an effect on Non-Financial Performance. Profitability mediates the effect of Working Capital and Asset Structure on Non-Financial Performance. Profitability does not mediate the effect of Operating Leverage on Non-Financial Performance. The result shows, that all proposed hypotheses are accepted except Hypothesis High Operating Leverage does not affect the Company's Non-Financial Performance. The company can grow and develop, and can increase the company's profitability by increasing its own capital and reducing some of the company's debt. Non-financial performance can be improved by providing fast, good, and satisfying service to consumers. Keywords —Working Capital; Asset Structure; Operating Leverage; Profitability; Non-Financial Performance